2022
DOI: 10.1177/0734242x221080097
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of end-of-life electric vehicle generation and analysis of the status and prospects of power battery recycling in China

Abstract: With the development of the electric vehicle (EV), vehicle end-of-life (EOL) management has become a significant challenge. This study sets two EV sales scenarios (low and high), compares the impact of two battery replacement methods (buying a new vehicle or replacing the battery) on future EOL EV production, and predicts the difference in the amount of EOL EV battery production under two probability functions (normal and Weibull’s distributions). The results show that when the EV power battery is retired and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 32 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Based on this knowledge, information, and expertise, this investigation addresses the current issues pertinent to ELV handling through critical analysis to prevent failure and enhance and standardize the processes involving ELV recycling to achieve the optimum standard for product and process quality. Qualitative research is instrumental in exploring current practices and issues and offering recommendations [31].…”
Section: Qualitative Datamentioning
confidence: 99%
“…Based on this knowledge, information, and expertise, this investigation addresses the current issues pertinent to ELV handling through critical analysis to prevent failure and enhance and standardize the processes involving ELV recycling to achieve the optimum standard for product and process quality. Qualitative research is instrumental in exploring current practices and issues and offering recommendations [31].…”
Section: Qualitative Datamentioning
confidence: 99%
“…Li et al [10] analyzed the current situation and prospects of WEVB recycling in China. Zou et al [11] suggested developing WEVB recycling in two respects: further strengthening the construction of a policy and standard system, and increasing support for WEVB recycling enterprises.…”
Section: Introductionmentioning
confidence: 99%